Green Paper on Land Reform: Overview and Challenges - Wian Erlank (Potchefstroom Electronic Law Journal, 2014)
Originating as a submission made to the Department of Rural Development and Land Reform by the Centre for Constitutional Rights in 2011, this paper provides an overview of some of the main aspects and key features that stem from the Green Paper on Land Reform, 2011. Following the framework of the Green Paper, this article provides a brief commentary on some of the most problematic aspects of the Green Paper, cross-referencing the key topics to the Green Paper itself as well as the other articles in the special edition of PER dealing with the Green Paper on Land Reform, 2011